2019
DOI: 10.1158/1078-0432.ccr-18-4083
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis in Cynomolgus Monkeys Following Treatment with Immune Checkpoint Inhibitors

Abstract: Purpose: Immune checkpoint inhibitors (ICI) targeting PD1, PDL1, or CTLA4 are associated with immunerelated adverse events (irAE) in multiple organ systems including myocarditis. The pathogenesis and early diagnostic markers for ICI-induced myocarditis are poorly understood, and there is currently a lack of laboratory animal model to enhance our understanding. We aimed to develop such a model using cynomolgus monkeys. Experimental Design: Chinese-origin cynomolgus monkeys were dosed intravenously with vehicle … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 44 publications
2
65
0
2
Order By: Relevance
“…The mechanism of ICI-related cardiac toxicity is not yet fully understood. Histological analyses of patients and monkey models with ICI-associated myocarditis have revealed that the infiltration of predominant CD4 + /CD8 + T lymphocytes and a few macrophages (CD68 + cells) are the main cause of ICI-associated myocarditis (Johnson et al, 2016a; Ganatra and Neilan, 2018; Ji et al, 2019) ( Figure 1 ). In addition, the expression change of multiple chemokine receptors further proves the enhancement of T cells.…”
Section: Potential Mechanism Of Immune Checkpoint Inhibitor-related Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of ICI-related cardiac toxicity is not yet fully understood. Histological analyses of patients and monkey models with ICI-associated myocarditis have revealed that the infiltration of predominant CD4 + /CD8 + T lymphocytes and a few macrophages (CD68 + cells) are the main cause of ICI-associated myocarditis (Johnson et al, 2016a; Ganatra and Neilan, 2018; Ji et al, 2019) ( Figure 1 ). In addition, the expression change of multiple chemokine receptors further proves the enhancement of T cells.…”
Section: Potential Mechanism Of Immune Checkpoint Inhibitor-related Cmentioning
confidence: 99%
“…In addition, the expression change of multiple chemokine receptors further proves the enhancement of T cells. CXCR3–CXCL9/CXCL10 and CCR5/CCL5 are required for T cell activities to upregulate (Tokunaga et al, 2018; Ji et al, 2019). Tumor necrosis factor-α, granzyme B, and interferon-γ are produced by activated T cells, inducing cell death.…”
Section: Potential Mechanism Of Immune Checkpoint Inhibitor-related Cmentioning
confidence: 99%
“…reported extensive inflammation in various organs (heart, hepatic, kidney, large intestine, adrenal medulla, and salivary glands) after ipilimumab and nivolumab treatment of monkeys. Interestingly, the myocarditis reported in monkeys demonstrated morphology, cardiac biomarker variations, and immune cell infiltrates comparable with human ICI-associated myocarditis ( Ji et al., 2019 ).…”
Section: Efforts To Uncouple Antitumor Immunity From Inflammation-drimentioning
confidence: 84%
“…The histopathological evaluation revealed that macrophages infiltrated in the cardiac tissue after ICIs treatment. 37 Macrophages are important cells that modulate inflammation. Indeed, under some circumstance, macrophages promote inflammation and extend injury, thus leading to cardiac senescence-related injury.…”
Section: Open Accessmentioning
confidence: 99%